Irritation Test and Effectiveness of Facial Humidity Skin from Peel Off Gel Mask Based of Date Palm Seeds Powder (Phoenix dactylifera) - Lestari, Uce; Farid, Faizar; Yuliawati, Yuliawati; Pratama, Septa (PUI BiGME Universitas Jambi, 2021)
Dry skin is the main problem of skin damage such as scaly, peeling, cracked and itchy skin, this is because the skin loses fluids due to weather changes and as we age we experience a decrease in the amount of oil and water on the skin. Facial skin care is done, one of which is by using a peel off gel mask of dates palm powder. The fat content is useful as a facial skin moisturizer. This study aims to determine the formula of the peel off gel mask which has determine its safety and effectiveness in moisturizing facial skin. The peel off gel mask was made into 3 formulas with the concentration of date palm seeds powder 1% (FI), 2% (FII) and 3% (FIII). Â Procedures in this study include irritation test, hedonic test and facial skin moisture test using a skin analyzer compared before and after use. Peel off gel mask choco milk as a positive control. The results showed that FII ( 2%) corresponding the requirements of no irritation occurs compared to other formulas. Testing the effectiveness of facial skin moisture showed that FII (2%) was able to increase the water content after use and the water content was higher than the positive control. Results it can be concluded that the FII has safe for use and effective in moisturizing facial skin.